Household Demand for Money in Poland : Theory and Evidence - Lane, Timothy (IMF Working Papers; Working Paper, 1992)
This paper examines the household demand for narrow money in Poland during the 1980s. At that time, there were shortages, but informal trade in both goods and foreign exchange was common, and holdings of foreign currency were substantial. Household money demand in this environment is first examined at the theoretical level: a representative household's holding of domestic and foreign money is analyzed in a cash-in-advance model in which domestic currency is needed to purchase goods in the official shops while either domestic or foreign currency can be used in the black market. This model gives rise to a formulation of money demand which is then estimated using household-level data from 1979 to 1988.